Ketahanan Tumbuh Permudaan Ramin di Genepool Ramin di SPTN Wilayah I Kawasan Taman Nasional Sebangau Kalimantan Tengah - Siti Maimunah; Nina Maryana (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2016)
Ramin’s growth and development is very slowly and have many inhibited factore, there are seed specific character with hard coating, too difficult for vegetative propagation, and limited abundant because seedling is very depend to sustainable nature, so there are caused how ramin is rare now. Ramin propagation have done in Sebangau National Park in 2010 with 5 ha wide area of Genepoolin two areas, 3ha area inSungai Koran and 2 ha in Stasiun Riset Lapangan (SSI). In Genepool area development hasn’t have database for growth and development of ramin.This research aim are to monitoring and evaluation growth endurance and to know how about ramin to decreasing in Genepool area. The parameter of this research is growth endurance, high, diameter and laef growth of Ramin seedling, pest and diseases. Growth endurance percentase for 5 year of growth is 60,70%, average of high 1,42 m, average of diameter 1,69 cm, average of leaf growth 17,61 helai, existence of pest and diseases is insecta attack and human activity. Need a socialiszationabout Genepool existence for minimizing ramin damaged caused human activities.